Infant feeding and treatment practices could lead to enhanced transmission of Kaposi's sarcoma-associated herpesvirus (KSHV) and other orally shed infections via saliva, in rural south-western Uganda - Dominic Bukenya; Vickie A. Marshall; Georgina Nabaggala; Wendell Miley; Miriam Mirembe; Denise Whitby; Janet Seeley; Robert Newton; Rosemary Rochford; Katherine R. Sabourin (Taylor & Francis Group, 2024)
This qualitative sub-study investigated household practices affecting orally shed infections using Kaposi's sarcoma-associated herpesvirus (KSHV) as a focus. Participants enrolled from 50 households in rural south-western Uganda were followed monthly up to three times. At enrolment, in-depth interviews were completed, and venous blood collected. KSHV seropositivity was defined as anti-KSHV antibody detection to any of 25 antigens by multiplex bead-based assay. Mouthwash samples from every visit were tested by qPCR and KSHV shedders defined as individuals with KSHV DNA detected. At least one KSHV seropositive person was in 48/49(98%) households. Among those, 79% had 1+ KSHV shedders including 45% with 1+ always shedders and 92% with 1+ intermittent shedders, not mutually exclusively. All respondents reported feeding infants with pre-masticated hard food/fruits and testing food/tea temperature. Temperature was tested by tasting, pouring tea on their hand, or touching the cup to their cheek. Some cooled food/tea using a utensil or blowing over it. Food sharing amongst children and adults and using the same dish was common practice. To treat colic pain, carers/mothers reported chewing herbs and spitting into the child's mouth. Feeding and treatment practices did not vary by KSHV status. We identified potential KSHV transmission modes in rural Ugandan households.